2016
DOI: 10.1016/j.ihj.2016.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of non-communicable diseases (NCD) risk factors in tribal district of Kinnaur, HP: A cross-sectional study

Abstract: Strengthening of primary health care services and community based interventions are urgently required to improve awareness and control of NCD risk factors in this tribal district of HP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 9 publications
4
43
1
Order By: Relevance
“…Obese individuals were more likely to have hypertension and diabetes mellitus compared with their counterparts. This finding was similar with previous study findings [47,48]. This might be due to the fact that obese people have excessive secretion of nonesterified fatty acids from adipose tissue which cause insulin resistance and β-cell dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Obese individuals were more likely to have hypertension and diabetes mellitus compared with their counterparts. This finding was similar with previous study findings [47,48]. This might be due to the fact that obese people have excessive secretion of nonesterified fatty acids from adipose tissue which cause insulin resistance and β-cell dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…The likelihood of having NCDs was higher among individuals who did low level of physical activity compared with their counterparts. This finding was in line with the study findings in Dabat, Ethiopia,[31], Jos, Nigeria [13] and India [47]. Low level of physical activity increase an overall positive energy balance, which directly contributes for the development of NCDs.…”
Section: Discussionsupporting
confidence: 90%
“…The rate of current tobacco use among this tribal population was 81.5%; higher than the reported figures for the rural (24.3%), urban (22.6%) and even the slum population (37.3%) in Kerala 9 . The overall rate of tobacco smoking (37.9%) and smoking rate among men (69.1%) were higher than the corresponding rates of (22.6%) and (47.9%) in the tribal district of Kinnaur of Himachal Pradesh 18 . As in the general population, smoking was more among men than women.…”
Section: Discussionmentioning
confidence: 71%
“…The prevalence of current alcohol consumption among the Kani tribe was 36.2%, which is slightly higher than the national prevalence (32%) 19 . Prevalence is much higher than rural, urban or slum population of Kerala and tribal districts of Kiannur of Himachal Pradesh 9, 18. Among the Kani tribes, prevalence of alcohol consumption among men and women were markedly higher than the general population of Kerala 9 .…”
Section: Discussionmentioning
confidence: 95%
“…[7] Nationwide surveys too revealed that among males smoking remained by far the most common form of tobacco consumption and among females chewing of zarda, dokta, etc. was the most common form of tobacco consumption in most parts of the country.…”
Section: Discussionmentioning
confidence: 99%